Single-cell sequencing reveals the tumor immune microenvironment in thyroid cancer: a narrow review - Liang, Kangcong; Wang, Ziyu; Zhang, Zhiqiang; Liu, Gengluan; Wang, Xidi; Cao, Heng; Zhong, Ming; Ye, Liping; Zhong, Xin; Xun, Jingyu; Lei, Kefeng; Li, Ningning (Frontiers in Immunology, 2026)
The immune microenvironment profoundly shapes the progression and therapeutic response of thyroid carcinoma. Through comprehensive analysis of single-cell RNA sequencing data, this review delineates the immune landscapes of papillary thyroid carcinoma (PTC), poorly differentiated thyroid carcinomas (PDTC), and anaplastic thyroid carcinomas (ATC), revealing a differentiation dependent trajectory of tumor immune microenvironment remodeling—from immune activation suppression coexistence in PTC, to immune exclusion in PDTC, and terminal exhaustion in ATC. This single-cell based approach enables high resolution dissection of cellular heterogeneity, immune crosstalk, and spatial organization that are often masked in bulk analyses. Such insights provide a scientific basis for precision immunotherapy, offering guidance for differentiation tailored strategies to overcome immune escape and improve clinical outcomes in thyroid cancer.